ANALISIS RESIKO MUSCULOSCELETAL DISORDER PADA TATA LETAK LCD PROYEKTOR RUANG KULIAH FAKULTAS EKONOMI & BISNIS UNIVERSITAS MURIA KUDUS - Akh Sokhibi; Rangga Primadasa (Universitas Ahmad Dahlan Indonesia, 2019)
A class room was a room where the face to face learning process took place in the form of lectures, discussions, tutorials, seminars, etc. The class room must be equipped with facilities and infrastructure including table and chair for lecturer and students, LCD projector and white board. The layout of equipment in the class room sometimes dis not consider the ergonomics aspects, so that it might cause musculoskeletal disorder to the students. Descriptive quantitative methods were used in this study. A randomsampling using the Nordic Body Map (NBM) questionnaire was used for data collection. Then, the data were analyzed by the contingency coefficient test which was interpreted in the form of a risk relationship picture of the musculoskeletal disorder in the class room of the Faculty of Economics and Business, Muria Kudus University. The results of thisreseartch were the LCD projector layout did not consider ergonomic aspects. The results of the Nordic Body Map Questionnaire showed that there were 14% high risk, 14% moderate risk and 72% small risk. There was a 14% relation between the location of the LCD Projector in the class room of the Faculty of Economics and Business, University of Muria Kudus, on the user's musculoskeletal disorder.